A modified 3D G-criterion for the prediction of crack propagation under mixed mode I-III loadings. (28th March 2023) - Shen, Zhen; Yu, Hongjun; Guo, Licheng; Hao, Liulei; Zhu, Shuai; Huang, Kai
Highlights: A modified 3D G -criterion is established for the mixed mode I-III crack. The new criterion differentiates the volumetric and distortional energy release rates and considers the influence of T -stress. The twist angles (critical SIFs) get increased (decreased) as the Poisson ratio increases. The negative (positive) T -stress will enhance (decrease) the critical SIFs. The critical SIFs reduce as the critical volumetric to distortional ERR ratio increases. Abstract: A modified 3D G -criterion is proposed for the crack under mixed mode I-III loadings, by differentiating the volumetric and distortional energy release rates (ERRs) and considering the influence of T-stress. The modified 3D G -criterion is validated by comparing the predicted tilt angle, twist angle and critical stress intensity factors (SIFs) with the experimental results for different materials. Then the effects of critical volumetric to distortional ERR ratio, Poisson ratio and dimensionless T-stress on the tilt angle, twist angle and critical SIFs are discussed. The tilt angle will be nonzero only when the dimensionless T-stress reaches a certain threshold, while the twist angle increases first and then gradually decreases as the dimensionless T-stress increases. Besides, the twist angle gets increased while the corresponding critical SIFs slightly decrease as the Poisson ratio increases. Finally, the critical SIFs are found to noticeably reduce as the critical volumetric to distortional ERR ratio increases, and get enhanced (decreased) when the dimensionless T-stress is negative (positive).